Length‐weight relationships of five lanternfishes (Myctophidae) from the high seas of Northwestern Pacific Ocean. (29th August 2018) - Wang, Liangming; Li, Yuan; Zhang, Ran; Tian, Yongjun; Lin, Longshan
Summary: The length‐weight relationships (LWRs) for five myctophid species were estimated, named Symbolophorus evermanni (Gilbert, 1905), Nannobrachium nigrum Günther, 1887, Ceratoscopelus warmingii (Lütken, 1892), Lampadena yaquinae (Coleman & Nafpaktitis, 1972) and Myctophum asperum Richardson, 1845. Specimens were collected using light‐purse seine (mesh size 3.5–4.5 cm) in the high seas of Northwestern Pacific in the spring of 2015 and the summer of 2016.